Ki-67 expression in pulmonary tumors - Chirieac, Lucian R. (Translational Lung Cancer Research; Vol 5, No 5 (October 31, 2016): Translational Lung Cancer Research (Liquid Biopsy in Lung Cancer)1, 2016)
Ki-67 was introduced more than two decades ago as a measure of the tumor proliferative fraction, in the need for a useful marker that might help clinicians to guide therapy and predict the prognosis of patients with cancer (1). Although several methods have been used to determine the tumor proliferative fraction in the research setting, the only practical methods used in the pathology laboratory were Ki-67 and mitotic count (2).